Torque-cadence profile and maximal dynamic force in cyclists: a novel approach - Rodríguez-Rielves, V.; Barranco-Gil, D.; Buendía-Romero, Á.; Hernández-Belmonte, A.; Higueras-Liébana, E.; Iriberri, J.; Sánchez-Redondo, I. R.; Lillo-Beviá, J. R.; Martínez-Cava, A.; de Pablos, R.; Valenzuela, P. L.; Pallarés, J. G.; et al. (Sensors, 2024)
We aimed to determine the feasibility, test-retest reliability and long-term stability of a novel method for assessing the force (torque)-velocity (cadence) profile and maximal dynamic force (MDF) during leg-pedaling using a friction-loaded isoinertial cycle ergometer and a high-precision power-meter device. Fifty-two trained male cyclists completed a progressive loading test up to the one-repetition maximum (1RM) on a cycle ergometer. The MDF was defined as the force attained at the cycle performed with the 1RM-load. To examine the test-retest reliability and long-term stability of torque-cadence values, the progressive test was repeated after 72 h and also after 10 weeks of aerobic and strength training. The participants` MDF averaged 13.4 ± 1.3 N·kg-1, which was attained with an average pedal cadence of 21 ± 3 rpm. Participants` highest power output value was attained with a cadence of 110 ± 16 rpm (52 ± 5% MDF). The relationship between the MDF and cadence proved to be very strong (R2 = 0.978) and independent of the cyclists` MDF (p = 0.66). Cadence values derived from this relationship revealed a very high test-retest repeatability (mean SEM = 4 rpm, 3.3%) and long-term stability (SEM = 3 rpm, 2.3%); despite increases in the MDF following the 10-week period. Our findings support the validity, reliability and long-term stability of this method for the assessment of the torque-cadence profile and MDF in cyclists.